a Hubungan Identitas Budaya dan Motivasi Akademik: Studi pada Mahasiswa Multietnis Indonesia dan Mesir - Hisyam Syafii; Azam Syukur Rahmatullah; Husain Azhari; Rudyn alaldaya (Universitas Negeri Jakarta, 2026)
This study investigates the relationship between cultural identity, cultural practices, cultural adaptation, and academic motivation among multiethnic students in Indonesia and Egypt, with a particular focus on the Indonesian context. Considering the unique academic challenges faced by students from diverse cultural and religious backgrounds, the study explores how cultural and Islamic values influence motivation and engagement. A cross-sectional quantitative design was employed, collecting data from 110 students aged 18–25 (55 from each country) using validated instruments, including the Multigroup Ethnic Identity Measure-Revised (MEIM-R), Cultural Practices Scale, and Academic Motivation Scale. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that cultural identity has the strongest positive effect on intrinsic academic motivation (β = 0.412, p < 0.001), followed by cultural practices (β = 0.218, p < 0.05), whereas cultural adaptation did not show a significant direct effect (β = 0.156, p = 0.059). Multi-group analysis revealed stronger relationships among Indonesian students (β = 0.521) than among Egyptian students (β = 0.298). These findings support Social Identity and Self-Determination theories and suggest that fostering positive cultural and Islamic values effectively enhances academic engagement. Practically, higher education institutions in Indonesia are encouraged to implement programs that integrate Islamic values, cultural awareness, and inclusive practices to strengthen students’ motivation, character, and academic success in multicultural learning environments.